2021
DOI: 10.1155/2021/3741104
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity Strength at Rest in Medication-Free Obsessive-Compulsive Disorder

Abstract: Background. Previous studies explored the whole-brain functional connectome using the degree approach in patients with obsessive-compulsive disorder (OCD). However, whether the altered degree values can be used to discriminate OCD from healthy controls (HCs) remains unclear. Methods. A total of 40 medication-free patients with OCD and 38 HCs underwent a resting-state functional magnetic resonance imaging (rs-fMRI) scan. Data were analyzed with the degree approach and a support vector machine (SVM) classifier. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Consistent with previous results [ 38 , 39 ], higher lpFCs in the left thalamus and right thalamus/caudate were observed in the current study. As a motor and sensory pathway and an important part of the cortical–striatal–thalamic–cortical (CSTC) circuit, the thalamus/caudate plays a crucial role in the regulation of behavior and cognition [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous results [ 38 , 39 ], higher lpFCs in the left thalamus and right thalamus/caudate were observed in the current study. As a motor and sensory pathway and an important part of the cortical–striatal–thalamic–cortical (CSTC) circuit, the thalamus/caudate plays a crucial role in the regulation of behavior and cognition [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have reported increased FC in the thalamus at rest ( 66 , 67 ). The increased FC of the thalamus is often interpreted as a compensatory brain activity that activates connected brain regions and enhances the ability of information integration ( 68 ). Recent studies have also shown increased FC between the regions of the FPN (DLPFC) and the thalamus in OCD and their first-degree relatives, in line with the findings in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) found that ReHo values increase in the right precuneus and decrease in the right PCC of patients with OCD. In addition, the FC, NH values, and GSR decrease in the PCC/PCu of patients with OCD (Chen et al., 2019; Lv et al., 2021; Peng, Xu, et al., 2014). In line with a study (Kraus et al., 2014) that found increased GMV and FC within the PCC/PCu after SSRI treatment, the present study found that the VMHC values of the bilateral PCC/PCu increase and that OCD clinical symptoms improve during treatment, suggesting the important role of the PCC/PCu in the therapeutic effects of SSRIs.…”
Section: Discussionmentioning
confidence: 99%